Practising development : social science perspectives - Pottier, Johan (Routledge, 1993)
Throughout the 1980s there have been calls, often from development organizations of global repute, for the incorporation of social science perspectives into the design and management of sustainable development programmes. Practising Development is the first collection to offer first-hand critical assessments of the success and failures found within actual responses to these calls. By combining academic and practical experience from anthropology, development and aid organizations the contributors examine the processes of intervention, the methods by which this intervention can be assessed, and.
Keywords: Applied anthropology.; Social sciences -- Methodology.; Community development -- Case studies.; Economic development projects -- Case studies.; Anthropologie appliquée.; Sciences sociales -- Méthodologie.; Développement communautaire -- Cas, Études de.; Projets de développement économique -- Cas, Études de.; Projets de développement économique -- Études de cas.; Développement communautaire -- Études de cas.; POLITICAL SCIENCE -- Public Policy -- City Planning & Urban Development.; Applied anthropology; Community development; Economic development projects; Social sciences -- Methodology; Angewandte Anthropologie; Aufsatzsammlung; Entwicklungsprojekt; Politikberatung; Sozialwissenschaften; Culturele antropologie.; Wetenschappelijke technieken.; Communities -- Development; Electronic books.; Case studies